Motivasi Mahasiswa Mengikuti Pemilihan Putera Puteri Kampus Riau - Sundari, Melda; Widodo, Teguh (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the motivation of students to participate in the Putera Puteri Kampus Riau election and also the benefits they achieve after participating in the event. This research uses qualitative research methods with a phenomenological approach. The subjects in this study amounted to six people according to predetermined criteria. Data collection techniques involved interviews and documentation. The results showed that the motivation of students to participate in the Putera Puteri Kampus Riau election was driven by the desire to increase their potential and achievement, recognition from others, seeing the success of others in similar events, the desire to build relationships and self-image, and wanting to influence others. The benefits they get after participating in the Putera Puteri Kampus Riau election are skill development, increased knowledge, offers of cooperation from sponsors, relationships and also increased knowledge and experience in leadership.